Modelagem do processo de eutrofização em um reservatório de clima tropical - Oliveira, Michele Araujo de (2025)
This study proposes the development of a new Trophic State Index (TSI) model for tropical environments, using the Tucuruí Hydroelectric Power Plant reservoir as a reference point, based on 14 years of data (2003–2016). To provide analytical validation of these results, two sampling campaigns were conducted during the rainy and dry seasons (March 2022 and October 2023). The Mann–Whitney test was applied to five sampling stations using as variables: total phosphorus, total pigments, and water transparency, along with the TSI defined by Lamparelli, to assess its effectiveness in determining the trophic status of the reservoir. Statistical analyses were performed at eight sampling stations distributed across all areas of the reservoir. Analyses covered both rainy and dry seasons and included the Shapiro–Wilk test for normality; Student’s t-test for normally distributed variables; and the Mann–Whitney test for non-normal variables. Relationships between variables were evaluated using simple linear regression with logarithmic transformation, and homoscedasticity and independence of residuals were assessed using the Breusch–Pagan and Durbin–Watson tests. A 5% significance level was adopted. Ordinary Kriging was also employed for spatial interpolation. The results of the analytical validation indicated that the medians and ranges observed in the samples collected in 2022 and 2023 fall within historical limits for all variables analyzed. A new TSI’ was developed, better suited to the reservoir’s conditions through the use of magnesium and total pigments as key variables. Ordinary Kriging enabled effective interpolation of the new index, confirming—across different seasonal periods—an appropriate trophic classification of the reservoir.